2013
DOI: 10.1007/s00774-013-0530-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with hydrogen molecules prevents RANKL-induced osteoclast differentiation associated with inhibition of ROS formation and inactivation of MAPK, AKT and NF-kappa B pathways in murine RAW264.7 cells

Abstract: The bone protective effects of the hydrogen molecule (H2) have been demonstrated in several osteoporosis models while the underlying molecular mechanism has remained unclear. Osteoclast differentiation is an important factor related to the pathogenesis of bone-loss related diseases. In this work, we evaluated the effects of incubation with H2 on receptor activator of NFκB ligand (RANKL)-induced osteoclast differentiation. We found that treatment with H2 prevented RANKL-induced osteoclast differentiation in RAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Previous studies reported that NF-kB was associated with osteoporosis as for its predominant role in osteoclastogenesis [31][32][33]. Here, our results demonstrated that NF-kB acts as a negative regulator in osteoblast differentiation, which also regulated the process of osteoporosis.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies reported that NF-kB was associated with osteoporosis as for its predominant role in osteoclastogenesis [31][32][33]. Here, our results demonstrated that NF-kB acts as a negative regulator in osteoblast differentiation, which also regulated the process of osteoporosis.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, AKT, the serineethreonine kinase, can function to either reduce or prevent cellular destruction from oxidants [45]. Extrinsic ROS overproduction inactivated AKT and related mTOR signals, increased apoptotic factor Bad activity and inhibiting anti-apoptotic factor BcL-2 [11,46]. In the present study, DM-mediated ROS overproduction significantly suppressed AKT phosphorylation, further lead to impaired osteoblast adhesion and morphology, decreased cell proliferation and ALP activity, and increased cytotoxicity and apoptotic injury, which were in accordance with some previous reports [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lines of evince support ROS and NO as cell signaling molecules in innate immune cells [35,36]. Interestingly, ROS produced by osteoclasts play a role in promoting the differentiation of these cells through Akt, NF-κB and ERK activation [37,38], suggesting that ROS function as a cell signaling mediator in osteoclastogenesis. Recent study reported that ROS-induced promotion of osteoclastogenesis is downmodulated by an antioxidant response system involving Nerf2 in the homeostatic context [39,40], indicating the presence of a sophisticated regulatory mechanism for ROS-associated osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%